Paleogeographic conditions for the accumulation of the Middle Callovian deposits in the Nikitino section (Ryazan Region) (Proceedings of Voronezh State University. Series: Geology, 2022)
Introduction: There are some discrepancies in the descriptions of layer 2 of Nikitino, one of the full sections of the Callovian tier in the Ryazan Region. The purpose of the article is to give a more detailed description of this layer and to reconstruct the burial conditions for invertebrate fauna in it. Methods: The work involved the study of rock and fauna samples selected from the Nikitino section. The total number of studied samples was 126. Results and discussion: 1) Discrepancies in the descriptions of layer 2 in the works of predecessors were analysed; 2) The structure of layer 2 was studied and a version of its formation was proposed; 3) The fauna remains were used to reconstruct the sedimentation conditions during the formation of the original sandstone layer. Conclusion: The new data allowed providing a more detailed description of the structure and conditions of the formation of layer 2. In particular, the rounded formations of layer 2 should be called sarsens rather than marl concretions. First, a layer of coarse-grained sandstone was formed. Then, it was eroded and redeposited in a younger sediment in the form of boulders. Sandstone accumulated in warm (16–21°C) shallow water (2–5 m). The water was saturated with oxygen. The salinity was about 35‰. Further research will make it possible to establish the conditions for the formation of all layers of the section.
Keywords: Callovian tier; paleogeography; Nikitino section; fauna; sedimentation conditions